Man's dominion : religion and the eclipse of women's rights in world politics - Jeffreys, Sheila. (Routledge, 2012)
"This book seeks to rekindle the criticism of religion as the founding ideology of patriarchy. Focusing on the three monotheistic religions: Judaism, Christianity and Islam, this book examines common anti-woman attitudes such as 'male-headship', impurity of women, the need to control women's bodies, and their modern manifestations in multicultural Western states"--Back cover.